## A Series Expansion of m(ex) Using Lambert's W Function

(The presentation that follows is a light introduction. For more austere results, consult Paper 1).

While looking for an analytic continuation of the hyper4 operator, one is tempted to search for series expansions for nx. Having such an expansion at hand may offer additional insight into what an analytic yx can look like, for y in R.

Instead of searching for an expansion of nx, it is often convenient to look for an expansion for n(ex) first. We are then faced with the following problem:

Let a series s with coefficients an be given: Determine the coefficients bn of the series expansion (initially disregarding issues of convergence) of s1 = es*x: The author posted the above problem to sci.math a little while ago, and here are two answers:

The first one, by Robert Israel: where the sum is over all sequences s = [s1, s2, s3, ... ] of nonnegative integers with: and the product is over those k for which sk > 0 (a finite set).

For example, the partitions of 4 correspond to s = [4,0...], [2,1,0...], [0,2,0...], [1,0,1,0...] and [0,0,0,1,0...], so:

b4 = a04/4! + (a02*a1)/(2!*1!) + a12/2! + a0*a2 + a3.

Robert has also provided Maple code to explicitly calculate the bn.

> b:=(n::nonnegint)->add( mul(a[q-1]^q/q!, q = map(j -> [j, numboccur(j,P)], convert(P,set))), P = combinat[partition](n));

The second one by Leroy Quet, from a simple differentiation property of exp(z):

bn=1, if n=0 else: Leroy derived the above recursive expression by noticing that if B(x) = exp(A(x)), then:

B'(x) = B(x) *A'(x). Ignoring temporarily issues of convergence inside a specified range, the expression follows by equating coefficients and changing indexes.

Both the above solutions are of course correct. Can we perhaps use either solution to calculate the series expansion of n(ex)? Yes we can. The author will use the second solution because it is easier to handle when using induction later on.

Before we proceed on calculating the coefficients, note that a simple inductive argument shows that all the iterates m(ex), m in N, are entire functions, so for any m in N, the corresponding series expansions converge for all x in R.

Now we need some consistent notation: The author will use am,n for the coefficients of the expansion of m(ex): In other words, m ranges in N = {1, 2, 3, ...} and n ranges in {0} U N = {0, 1, 2, 3, ...}. The coefficients of ex then will be: {a1,0, a1,1, a1,2,...}. The coefficients of 2(ex) will be: {a2,0, a2,1, a2,2,...}, etc.

The recursion then becomes: It is immediately clear that am,0 = 1, for all m in N.

Since we are also in possession of the coefficients of ex, the recursion is complete, and we can immediately write Maple code to generate any am,n.

> a:=proc(m,n)
> option remember;
> local j;
> if n=0 then 1
> elif m=1 then 1/n!
> fi;
> end:

Here's a table with the coefficients of xn in the series expansions for the first few m(ex):

 am,n 0 1 2 3 4 5 6 1 1 1 1/2 1/6 1/24 1/120 1/720 2 1 1 3/2 5/3 41/24 49/30 1057/720 3 1 1 3/2 8/3 101/24 63/10 6607/720 4 1 1 3/2 8/3 125/4 49/5 12847/720 5 1 1 3/2 8/3 125/4 54/5 16087/720 6 1 1 3/2 8/3 125/5 54/5 16807/720

The keen eye will notice the pattern that emerges. But before we actually investigate it, let us prove that there is a pattern, whatever it is:

Lemma:

am,n = an,n, for all m ≥ n.

Proof:

By induction on n. It is clear that a1,1 = 1 and am,0 = 1 for all m in N. If ak,1 = 1 then ak+1,1 = Σ11j*ak+1,1-j*ak,j-1/1 = ak+1,0*ak,0 = 1 = a1,1.

Therefore, am,1 = a1,1 for all m in N.

Now assume am,k = ak,k is true for all m ≥ k.

We have to show that am,k+1 = ak+1,k+1 for all m ≥ k+1. However:

am,k+1 = Σ1k+1j*am,k+1-j*am-1,j-1/(k+1)

ak+1,k+1 = Σ1k+1j*ak+1,k+1-j*ak,j-1/(k+1)

m ≥ k+1 => m ≥ k+1-j, for all j in {1..k+1}, so am,k+1-j = ak+1-j,k+1-j, by the induction hypothesis. (1)

k+1 ≥ k+1-j, for all j in {1..k+1}, so ak+1,k+1-j = ak+1-j,k+1-j, again by the induction hypothesis. (2)

(1) and (2) establish: am,k+1-j = ak+1,k+1-j.

j ≤ k+1 => j-1 ≤ k and m ≥ k+1 => m-1 ≥ k, so j-1 ≤ m-1, so am-1,j-1 = aj-1,j-1, by the induction hypothesis as well. (3)

And finally: j ≤ k+1 => j-1 ≤ k, so ak,j-1 = aj-1,j-1, by the induction hypothesis. (4)

(3) and (4) establish: am-1,j-1 = ak,j-1 and we are done.

So, the coefficients eventually "stabilize". To what though? Well, here comes the surprise. Assuming that limn->+∞nx converges, it converges to e-W(-log(x)), as established in article 1. Therefore assuming that limn->+∞n(ex) converges, it converges to e-W(-log(exp(x))). But this is e-W(-x). And if we use Lambert's W function's alternate definition, this is W(-x)/(-x).

Now, knowing that the series expansion for the Lambert's W function is: it follows immediately that whenever we have convergence, W(-x)/(-x) is: Now we know exactly what those coefficients am,n in the expansion of m(ex) will be. To summarize:

For m = 1:

m(ex) = ex, of course.

For m > 1:

m(ex) = with: .

And here is the corresponding Maple code to calculate the series expansions of the iterates m(ex), given m and x:

> a:=proc(m,n)   #coefficients calculation
> option remember;
> local j;
> if n=0 then 1
> elif m=1 then 1/n!
> fi;
> end:

> f:=proc(m,x)  #expansion as per above
> local s1,s2;
> s1:=1+sum('(n+1)^n/(n+1)!*x^n','n'=1..m);
> s2:=sum('a(m,n)*x^n','n'=m+1..100);
> s1+s2;
> end:

> g:=proc(m,x) #for comparison
> if m=1 then exp(x)
> else exp(x*g(m-1,x));
> fi;
> end:

Let's do some comparisons:

> evalf(g(2,0.12345));
1.149894868

> evalf(f(2,0.12345));
1.149894869

> evalf(g(10,0.22));
1.344055119
> evalf(f(10,0.22));
1.344055119

> evalf(g(10,exp(-1)));
2.320458538

> evalf(f(10,exp(-1)));
2.320454949

> evalf(g(10,0.33*I));
.8788015388 + .2622477964 I

> evalf(f(10,0.33*I));
.8788015388 + .2622477963 I

> evalf(g(20,exp(-1)*I));
.8576167143 + .2799279251 I

> evalf(f(20,exp(-1)*I));
.8578364601 + .2796999407 I

So we have a sequence of entire functions fm(x) = m(ex), which converge to the limit function: f(x) = e-W(-x).

It is easy to see via the Ratio Test that the radius of convergence of the limit function: f(x) is: R = 1/e.

Because of the above fact, it is natural to expect "bad" convergence behavior around 1/e in the corresponding series expansions of the functions fm(x). What this means, is that while the Maple code above works perfectly for |x| ≤ 1/e, all the corresponding series expansions will most likely misbehave for values of x of the form: x = 1/e + dx(m), where dx(m) > 0, and dx(m) is a function of m. If we were to describe the situation in very rough terms, we could say that the series expansion for fm(x) will "misbehave" around 1/e + dx(m), with dx(m) -> 0 as m -> +∞. And this is to be expected. If convergence of the series expansions of the iterates: m(ex) was everywhere nice, the limit function would be entire. But it's not.

Notes/References

1. Compare with the radius of convergence of W, here. 